EU regulation on "conflict minerals": A step towards higher accountability in the extractive sector? - Karin Küblböck; Hannes Grohs (Austrian Foundation for Development Research (ÖFSE), 2017)
"No blood in my cell phone" - In the early 2000s, NGO-campaign slogans pointed out the links between raw materials in electronic products and the financing of armed conflicts. These campaigns focused on the responsibility of companies for their supply chain. In July 2017, an EU regulation came into effect that aims to prevent companies from financing armed conflicts via their procurement of raw materials. This Policy Note explains how the debates on 'conflict minerals' led to the formulation of various regulatory initiatives and analyses the scope and potential impact of the current EU-regulation.
Keywords: 330